RELEVANSI PEMIKIRAN SEYYED HOSSEIN NASR TENTANG INTEGRASI ISLAM DAN SAINS TERHADAP PENDIDIKAN ISLAM DI INDONESIA - Muhammad, Abduh; Kerwanto (LPPM Institut Nida El-Adabi, 2023)
This article aims to analyze the thoughts of Seyyed Hossein Nasr regarding the integration of Islam and science, and their relevance to Islamic Education, especially in Indonesia. The method used in this research is literature study where the writer tries to find, compile and analyze various information through various related sources. The results of this study explain that according to Seyyed Hosein Nasr Muslims do not have to lose their spiritual roots, in order to gain progress in science and technology. According to Nasr view, Islam and science cannot be separated, even Islam in itself wants the progress of science. This thought is not only in the epistemological concept, but also in the ontological realm, related to human existence itself, as well as the axiological realm that determines ethical aspects in human life. It was found that Seyyed Hossein Nasr's paradigm of the integration of Islam and science has an urgency and relevance especially for the implementation of Islamic Education in Indonesia. By offering a sufistic traditionalist approach, which is the root of the Islamic spirituality tradition, it is hoped that it will be able to provide a moral and ethical foundation in the process of Islamic education in Indonesia. Integration of Islam and Science which is not only in the object of knowledge, but unites in humans, as subjects of knowledge, human learners.